Digital Natives and the Advantages of their Generation to the Business World - Egbon, Thomastina Nkechi; Okolie, Ugo Chuks (Universitas Kuningan, 2024)
The divide between individuals who were brought up with technological devices (digital natives) and those who possess not (digital immigrants) is getting wider as a result of the ongoing advancement of technological devices. However, this gap is present in the business sector today. As a result, this study investigates the traits and actions of digital natives in the business world. This study used an analytical approach, depending on secondary data and content analysis to interpret the data that was collected. According to the study's conclusion, businesses that recognise and value the potential of digital natives will be more competitive in the long run. In order to accomplish this, managers must interact with this generation using novel, frequently nuanced techniques and behaviours. This does not imply that everything businesses have done in past decades to attract as well as retain talent is no longer relevant. However, we must expand our toolkits and alter our work cultures and beliefs.